Students’ Spatial Ability Profile in Solving Elementary School Geometry Probelms - Anggita Rachmawati; Joko Siswanto; Iin Purnamasari (Mimbar Ilmu, 2025)
Students’ mathematical competence in geometry remains low, as reflected in unsatisfactory PISA results and exam scores below the minimum standard. This issue is exacerbated by teacher-centered instruction and limited use of concrete media to develop spatial skills at the concrete operational stage.This study aims to analyze the profile and utilization of students’ and teachers’ spatial abilities in solving geometry problems. The study involved 9 students and 3 teachers, with data collected through interviews, tests, observations, and Focus Group Discussions (FGDs). The research employed a qualitative approach to explain phenomena in depth through non-numerical data, including verbal responses, visual representations, and observational findings. The results indicate that students’ spatial ability profiles generally fall within the “fair” or “moderate” category. Students with high mathematical ability demonstrated stronger mastery, particularly in aspects of spatial visualization and mental rotation. However, the main challenges faced by students include difficulties in constructing three-dimensional shapes and accurately determining geometric measurements. Overall, spatial ability requires focused attention and more targeted instructional strategies to be effectively enhanced. To address these challenges, teachers are strongly encouraged to implement scaffolded, practical, and interactive learning strategies by utilizing concrete media and technological tools such as GeoGebra. Such approaches are expected to bridge the gap between abstract geometric concepts and students’ concrete understanding, in alignment with the stages of thinking development proposed by Van Hiele’s theory.